Analisis Windrose Sebagai Input Prediksi Pencemaran Udara Menggunakan Software AERMOD - Parlaungan Hasibuan; Aryo Sasmita; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
PM2.5 pollutant are very harmful to human because it has a very small size which can infect the human lungs easily. Distribution of particulate is very difficult to seen by human eyes. One of the ways to know distribution of particulate besides direct measurement in the field is using a model. The model used is AERMOD VIEW. This research was conducted to know the pattern of emission distribution from boiler and incinerator chimney in annual scenario by doing windrose analysis. The results of modeling show distribution of pollutant tends leads to the southeast and north from PTPN V Sei Galuh. Distribution of particulate from the source is affected by wind direction characteristic.Keywords: AERMOD VIEW, PM2.5, palm oil industry.